Prescribing quality indicators of type 2 diabetes mellitus ambulatory care. Issue 5 (8th October 2008) - Martirosyan, L; Braspenning, J; Denig, P; de Grauw, W J C; Bouma, M; Storms, F; Haaijer-Ruskamp, F M
Abstract : Background: Existing performance indicators for assessing quality of care in type 2 diabetes mellitus (T2DM) focus mostly on registration of measurements and clinical outcomes, and not on quality of prescribing. Objective: To develop a set of valid prescribing quality indicators (PQI) for internal use in T2DM, and assess the operational validity of the PQI using electronic medical records. Methods: Potential PQI for hypertension, hyperglycaemia, dyslipidaemia and antiplatelet treatment in T2DM were based on clinical guidelines, and assessed on face and content validity in an expert panel followed by a panel of GPs and diabetologists. Analysis of ratings was performed using the RAND/UCLA Appropriateness Method. The operational validity of selected indicators was assessed in a dataset of 3214 T2DM patients registered with 70 GPs. Results: Out of 31 potential prescribing indicators, the expert panel considered 18 indicators as sufficiently valid, of which 14 indicators remained valid after assessment by the panel of GPs and diabetologists. Of these 14 indicators, one could not be calculated because of an absence of eligible patients. For the remaining indicators, outcomes varied from 10% for timely prescribing of insulin to 96% for prescribing of any antihyperglycemic medication in patients with elevated HbA1c levels. Conclusions: This study provides a set of face- and content-valid PQI for pharmacological management of patients with T2DM. While outcomes of some PQI were limited to patients with registration of clinical values, the selected PQI had good operational validity to be used in practice for assessment of prescribing quality.